Effects of drought stress on growth, grain filling duration, yield and quality attributes of barley (Hordeum vulgare L.) - Alghabari, Fahad; Ihsan, Muhammad Zahid (Bangladesh Journal of Botany, 2018)
A pot experiment was conducted to investigate the effect of drought stress at start of anthesis (applied by adjusting the field capacities at 100, 50 and 30%) on barley growth, grain filling duration, grain shape, yield and quality attributes. The effect of drought stress was more prominent on plant fresh biomass accumulation, grain yield and grain filling duration. However, it produced non-significant effect on total number of tillers and grain protein contents. With the increasing intensity of drought stress, barley growth and yield traits significantly diminished. Water stress gradually shortened the plant height and biomass accumulation but the difference was more prominent in fresh biomass accumulation (– 45%) over dry biomass accumulation. The field capacity of 30% caused 29 - 41% reduction in leaf chlorophyll content and 10 - 27% in grain quality traits. Root fresh and dry biomass accumulation decreased by drought stress while root length increased. Drought stress produced uneven grain size that resulted in lower grain yield (42%) specially at 30% field capacity. This reduction in yield was also due to the decreased grain filling duration (38 d) at 30% field capacity as compared to 100% field capacity. So, it may be concluded that drought stress affected barley yield through impaired grain development and grain filling duration. The results of present study are satisfactory and needed further exploration about the physiological mechanism and management strategies to overcome drought stress related yield losses in barley crop.